Ferrocene-modified Uio-66-NH2 hybrids with g-C3N4 as enhanced photocatalysts for degradation of bisphenol A under visible light - Huang, Zhikun; Yu, Haojie; Wang, Li; Liu, Xiaowei; Ren, Shuning; Liu, Jinyi (Journal of hazardous materials, 2022)
Designing graphitic carbon nitride (CN) based heterostructured photocatalysts with high catalytic activity is highly desired for peroxymonosulfate (PMS) activation to degrade organic pollutants from water. Herein, a novel heterostructured composite (U-F@CN) consisting of ferrocene-modified Uio-66-NH2 (U-F) and CN was synthesized. The U-F@CN exhibited superior photocatalytic performance to degrade bisphenol A (BPA) in the presence of PMS under visible light. The experimental results indicated that BPA could be removed entirely by U-F@CN within 60 min under visible light irradiation. In addition, the outstanding photocatalytic activity could be maintained at high level in a wide pH range, appropriate temperature region and natural water condition. Benefiting from the good chemical stability, outstanding optical property and in-situ generation of interfacial heterojunction of U-F@CN, the interfacial transport of photogenerated charges could follow the Z-scheme mechanism, which can accelerate the charge separation and transport to yield abundant reactive active species (ROS) to efficiently active PMS and under visible light. This work provides a novel approach to design CN-based heterostructured photocatalysts with high stability and superior photocatalytic activity for environmental remediation. [Display omitted] •The Fc group was grafted on the ligands of Uio-66-NH2via –C=N- covalent bond.•The chemical environment of U-F-X was directly proofed.•The Z-scheme heterojunction mechanism of BPA degradation was confirmed.